STUDY OF PLANT TOPING AND GROWING MEDIA COMPOSITION ON GROWTH AND YEALD OF MELON WITH HYDROPONIC DRIP SYSTEM - Ery Anggono; Endah Budi Irawati; Darban Haryanto (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2018)
This research aims to find out the influence of toping on each melon tree towards the yield of melon, and the influence of the use of various growing media compositions towards the yield of melon. This research is conducted in green house at Kaliurang Street km 16.3, Umbulmartani, Pakem, Sleman Regency, the Special Region of Yogyakarta. The research was held when august to October 2017. The research method used is Field Trial which is arranged by using Complete Randomized Design with two treatment factors and is repeated three times. The first factor is the use of growing media in the form of husk charcoal and zeolite (100% : 0%), (85% : 15 %), (70% : 30%), and (55% : 45%). The second factors are performing toping and not performing toping. Based on the analysis, it is shown that there is no interaction between growing media composition and toping treatment based on growing parameters or yield. The growing media composition with husk charcoal and zeolite (85% : 15%) shows a good result in affecting the parameters of fruit weight and fruit diameter. Toping treatment gives a good result for the parameters of fruit weigh, fruit diameter, brix, and flesh thickness.Keywords: melon, toping, growing media composition, hydroponic drip system